Le tecnologie di rilievo marino e costiero (GEOmedia, 2015)
In a quiet location on the banks of the Tiber River, not far from the airport "Leonardo Da Vinci" of Rome, on October 9 and 10, was held a workshop entitled "The marine and coastal survey technologies" organized by Codevintec.